2000
DOI: 10.1159/000055638
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Particle Size of Polymeric Nanospheres on Intravitreal Kinetics

Abstract: In this study, we injected nanospheres containing a fluorescein derivative into the vitreous cavity of pigmented rabbit eyes and evaluated their intraocular kinetics as drug carriers in vivo. Polystyrene nanospheres (2 µm, 200 nm and 50 nm in diameter) containing a fluorescein derivative were used in this study. A suspension of each particle was prepared by diluting with distilled water at a concentration of 10 µg/ml equivalent to sodium fluorescein. The suspension of nanospheres was injected once into the vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
1
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(78 citation statements)
references
References 16 publications
(10 reference statements)
3
70
1
2
Order By: Relevance
“…43 In vivo, it was reported that PLGA NPs injected into the vitreous of rat eyes followed a 'trans-retinal pathway' and underwent a rapid internalization into the RPE cells layer. 72,76 In our study, we also observed that most NPs encapsulating the pDNA injected in the vitreous localized within the RPE cells, and the expression of the GFP protein was detected as early as the third day after injection and remained detectable for at least 4 weeks by fluorescence microscope.…”
Section: Pdna-loaded Nanoparticles Inhibit Cnv C Zhang Et Alsupporting
confidence: 66%
“…43 In vivo, it was reported that PLGA NPs injected into the vitreous of rat eyes followed a 'trans-retinal pathway' and underwent a rapid internalization into the RPE cells layer. 72,76 In our study, we also observed that most NPs encapsulating the pDNA injected in the vitreous localized within the RPE cells, and the expression of the GFP protein was detected as early as the third day after injection and remained detectable for at least 4 weeks by fluorescence microscope.…”
Section: Pdna-loaded Nanoparticles Inhibit Cnv C Zhang Et Alsupporting
confidence: 66%
“…Although a previous study using primates has suggested that molecules exceeding 100 kDa cannot cross the retinal layers into the subretinal space [49], it has been confirmed by immunohistochemical analysis, a full-length, humanized, anti-vascular endothelial growth factor (VEGF) monoclonal antibody (Bevacizumab, Avastin ® , Genentech Inc.), composed of 214 amino acids with a molecular weight of 149 kDa, injected into the vitreous cavity, can penetrate through the sensory retina into retinal pigment epitheliums (RPE), subretinal and choroidal space, in monkey and rabbit [50,51]. In addition, nanometer-sized particles whose mean diameter is below 200 nm can penetrate across the sensory retina into RPE after intravitreal injection in rabbit [52,53].…”
Section: Retinamentioning
confidence: 99%
“…When fluorescent 2000 nm, 200 nm, and 50 nm nanospheres were injected into the vitreous body of rabbits, the 2000 nm particles were found in the intravitreal cavity and the trabecula, whereas the 200 nm and 50 nm particles were found even inside the retina. 60 When devices that are non-degradable in vivo are used, drug release is stable for a long period, but surgical removal of the device after sustained drug release is generally difficult to achieve. When biodegradable implants are used, they do not need to be removed after sustained drug release; however, in comparison with implants that are non-biodegradable in vivo, intravitreal drug concentration is unstable, and the sustained-release period is shorter.…”
Section: Micro/nanospheresmentioning
confidence: 99%